Analysis of Factors Associated with Husband's Involvement in Becoming Family Planning Acceptors in Unaaha District, Konawe Regency in 2022 - Masnawati; Sartiah Yusran; Wa Ode Salma (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the factors related to the husband's involvement as a family planning approval provider in Unaaha District, Konawe Regency in 2022. This type of research is an analityc observation research with a case-control approach. The number of samples used is 106 people with a comparison of 53 people as a control sample and 53 as a case sample. In general, all the variables that are most dominant at risk of not participating in husbands becoming male family planning acceptors are family support variables because the highest Exp (B) value is 21.388 times the risk if the husband has poor family support. As well as having the smallest p-value of 0.019